Association Between Frailty and Dietary Diversity in Korean Elderly: Based on the 2018 Korean National Health and Nutrition Examination Survey. (7th June 2021) - Kim, Jungeun; Yang, Suhyeon; Kim, Hyesook; Chang, Eugene; Kim, Yangha
Abstract: Objectives: Frailty is a clinical syndrome in older adults. Adequate nutrition is a modifiable factor in preventing frailty. The purpose of this study was to investigate the association between frailty and dietary intake in Korean elderly. Methods: This study used raw data from the 2018 Korea National Health and Nutrition Examination Survey. Study subjects were 1268 (535 of men and 733 of women). Frailty was defined as having three or more of the following five criteria including unintentional weight loss, weakness, waking difficulties, exhaustion and low physical activity. Pre-frail was defined as having one or two criteria. Robust was defined as having none of the criteria. Dietary intake was assessed by a one-day 24 h dietary recall. The food variety score (FVS) was defined as the number of food items consumed by each subject during the last 24 h. Results: In this study, 9.7% of men and 21.9% of women were classified as frail group. Intake of energy, macronutrients and micronutrients was significantly low in frail men and women. Also, total food intake was significantly low in frail men and women. In men, the odds ratio (95% CI) of frailty for those in the highest tertile compared with the lowest tertile of food intake were 0.34 (0.13–0.93) for fruits. In women, the odds ratio (95% CI) of frailty for those in the highest tertile compared with the lowest tertile of food intake were 0.57 (0.35–0.93) for potatoes and 0.55 (0.30–0.99) for fish and shellfish. In addition, subjects with higher mushroom intake had lower risk of frailty 0.31 (0.12–0.78) in consumer and 0.41 (0.22–0.79) in non-consumer after adjustment for all potential covariables. Conclusions: These results suggested that diverse diets composed with five major food groups may have preventive effect against the risk of frailty among Korean elderly. Funding Sources: This research was supported by the BK21 FOUR (Fostering Outstanding Universities for Research) funded by the Ministry of Education(MOE, Korea) and National Research Foundation of Korea(NRF).